First record of Xylophallus xylogenus (Phallaceae, Agaricomycetes) in Central Brazil: morphological notes and habitat observations - Machado, Tullyo Henrique Lima; Menezes Filho, Antonio Carlos Pereira de; Ventura, Matheus Vinícius Abadia (Brazilian Journal of Science, 2025)
This study presents the first documented occurrence of Xylophallus xylogenus in the Central-West Region of Brazil, specifically in Itapaci, Goiás. Ten specimens were collected on April 17, 2025, from soil containing decomposing rice straw. The macroscopic and ecological characteristics matched previous descriptions of the species. This finding expands the known geographic distribution of this rare and poorly collected member of the Phallaceae and contributes to the ongoing documentation of Neotropical fungal diversity.